2022
DOI: 10.1111/bjh.18129
|View full text |Cite
|
Sign up to set email alerts
|

Clonal haematopoiesis as a risk factor for therapy‐related myeloid neoplasms in patients with chronic lymphocytic leukaemia treated with chemo‐(immuno)therapy

Abstract: Clonal haematopoiesis of indeterminate potential (CHIP) may predispose for the development of therapy-related myeloid neoplasms (t-MN). Using target nextgeneration sequencing (t-NGS) panels and digital droplet polymerase chain reactions (ddPCR), we studied the myeloid gene mutation profiles of patients with chronic lymphocytic leukaemia (CLL) who developed a t-MN after treatment with chemo-(immuno)therapy. Using NGS, we detected a total of 30 pathogenic/likely pathogenic (P/LP) variants in 10 of 13 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Furthermore, FCR should be particularly avoided in patients with clonal hematopoiesis of indeterminate potential (CHIP), as they have an even higher risk of developing myeloid malignancies. 42 In the current era, patients without adverse prognostic features could experience an excellent prognosis also with novel agents without the risk of a treatment-related myeloid malignancy. 41 , 43 Our findings indicate that we could reduce the incidence of treatment-related myeloid malignancies by simply omitting FCR from CLL treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, FCR should be particularly avoided in patients with clonal hematopoiesis of indeterminate potential (CHIP), as they have an even higher risk of developing myeloid malignancies. 42 In the current era, patients without adverse prognostic features could experience an excellent prognosis also with novel agents without the risk of a treatment-related myeloid malignancy. 41 , 43 Our findings indicate that we could reduce the incidence of treatment-related myeloid malignancies by simply omitting FCR from CLL treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, 30 pathogenic or likely pathogenic variants were identified in 77% of patients who later developed t-MN, compared to 12% of patients in the control group who received the same treatment. Remarkably, upon retrospective analysis, the same variants were identified in 62.5% of patients at the time of CLL diagnosis, suggesting their pre-existing and clonal nature [45].…”
Section: The Role Of Clonal Hematopoiesismentioning
confidence: 84%
“…However, it is essential to keep in mind that also putative tumor-free material (i.e. saliva or CD19 negative blood cells) can be contaminated by CLL cells [ 103 ], active myeloid malignancy precursors (e.g., therapy-related myelodysplastic syndrome [ 104 ] or myeloproliferative neoplasm) or clonal hematopoiesis of indeterminate potential. Allelic frequency of >30% (SNVs) or >20% (small insertions/deletions) in non-tumor tissue is expected for variants of germline origin [ 100 ], and lower VAFs are indicative of cancer cell contamination or, rarely, mosaicism.…”
Section: Interpretation Of the Results And Reportingmentioning
confidence: 99%